Spontaneous resolution of conjunctival hemorrhagic lymphangiectasia - Nagaoka, Kosuke; Makino, Shinji (Digital Journal of Ophthalmology, 2025)
Conjunctival hemorrhagic lymphangiectasia is a rare condition in which the lymphatic channels in the bulbar conjunctiva are dilated and filled with blood. A healthy 7-year-old girl with no past medical history presented at Jichi Medical University Hospital with redness and swelling in her left eye. Slit-lamp examination revealed hyperemia and a wormlike, blood-filled conjunctival lymphatic vessel in the superotemporal bulbar conjunctiva (A). The clinical findings were consistent with a diagnosis of conjunctival hemorrhagic lymphangiectasia. The patient was followed without treatment. At a follow-up visit 3 weeks later, the hemorrhagic conjunctival lymphangiectasia had resolved (B).